Global Monitoring Report, 2009 : A Development Emergency. (World Economic and Financial Surveys; World Economic and Financial Surveys, 2009)
A Development Emergency: the title of this year's Global Monitoring Report, the sixth in an annual series, could not be more apt. The global economic crisis, the most severe since the Great Depression, is rapidly turning into a human and development crisis. No region is immune. The poor countries are especially vulnerable, as they have the least cushion to withstand events. The crisis, coming on the heels of the food and fuel crises, poses serious threats to their hard-won gains in boosting economic growth and reducing poverty. It is pushing millions back into poverty and putting at risk the very survival of many. The prospect of reaching the Millennium Development Goals (MDGs) by 2015, already a cause for serious concern, now looks even more distant. A global crisis must be met with a global response. The crisis began in the financial markets of developed countries, so the first order of business must be to stabilize these markets and counter the recession that the financial turmoil has triggered. At the same time, strong and urgent actions are needed to counter the impact of the crisis on developing countries and help them restore strong growth while protecting the poor. Global Monitoring Report 2009, prepared jointly by the staff of the World Bank and the International Monetary Fund, provides a development perspective on the global economic crisis. It assesses the impact on developing countries, their growth, poverty reduction, and other MDGs. And it sets out priorities for policy response, both by developing countries themselves and by the international community. This report also focuses on the ways in which the private sector can be better mobilized in support of development goals, especially in the aftermath of the crisis.